Hibridaciones y subversiones al desarrollo: una mirada desde lo andino y lo afroamericano - Arévalo-Robles, G. Andrés (Revista Española de Desarrollo y Cooperación, 2023)
The development is shown as something neutral, natural and universal but actually it constitutes an unheard way of power. In the presence of the failure of development policies it is worth to investigate other social projects that are able to subvert the concept of development. The present article tries to introduce the main debates of development and tries to prove other visions and interpretations of the social life, specifically the andine stance and the experience of the african descendants’ communities in the Colombian Pacific.